2013
DOI: 10.1371/journal.pone.0073521
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Morphological and Molecular-Based Surveys to Estimate the Species Richness of Chaetoceros and Thalassiosira (Bacillariophyta), in the Bay of Fundy

Abstract: The goal of this study was to compare the ability of morphology and molecular-based surveys to estimate species richness for two species-rich diatom genera, Chaetoceros Ehrenb. and Thalassiosira Cleve, in the Bay of Fundy. Phytoplankton tows were collected from two sites at intervals over two years and subsampled for morphology-based surveys (2010, 2011), a culture-based DNA reference library (DRL; 2010), and a molecular-based survey (2011). The DRL and molecular-based survey utilized the 3′ end of the RUBISCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…All eight strains shared the same percent identity (PID, which was used to quantify the similarity between the biomolecular sequence) (99.94%) when compared to the reference sequence of E. zodiacus on full-length 18S rDNA ( Sorhannus, 2007 ). Similar high PIDs were found for other molecular markers including 28S rDNA D1-D2 (100%) ( Hamsher et al, 2013 ), ITS (99.28%) ( Guo et al, 2015 ), CO1 (99.25%) ( Guo et al, 2015 ), and rbcL (100%) ( Guo et al, 2015 ), respectively. Phylogenetic analysis of molecular marker sequences obtained for all eight strains indicated that they all clustered well with corresponding E. zodiacus sequence records at GenBank ( Supplementary Figure S1 ), further confirming that these strains were all indeed E. zodiacus .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…All eight strains shared the same percent identity (PID, which was used to quantify the similarity between the biomolecular sequence) (99.94%) when compared to the reference sequence of E. zodiacus on full-length 18S rDNA ( Sorhannus, 2007 ). Similar high PIDs were found for other molecular markers including 28S rDNA D1-D2 (100%) ( Hamsher et al, 2013 ), ITS (99.28%) ( Guo et al, 2015 ), CO1 (99.25%) ( Guo et al, 2015 ), and rbcL (100%) ( Guo et al, 2015 ), respectively. Phylogenetic analysis of molecular marker sequences obtained for all eight strains indicated that they all clustered well with corresponding E. zodiacus sequence records at GenBank ( Supplementary Figure S1 ), further confirming that these strains were all indeed E. zodiacus .…”
Section: Resultssupporting
confidence: 75%
“…Many common molecular markers of E. zodiacus including 18S rDNA, 28S rDNA, ITS, rbcL , and CO1 have been sequenced and applied to characterize E. zodiacus ( Sorhannus, 2007 ; Rampen et al, 2009 ; Sorhannus and Fox, 2011 ; Ashworth et al, 2013 ; Hamsher et al, 2013 ; Guo et al, 2015 ). However, these molecular markers have not been evaluated for their ability to study intra-species genetic diversity of E. zodiacus .…”
Section: Introductionmentioning
confidence: 99%
“…exiguus was reported in samples from Cape Wankarema and the Kara Sea (Grunow 1884). It was also registered in the Saint Laurent Gulf (northern Canada) and Arctic regions by Bérard-Therriault et al (1999), as well as in the Bay of Fundy by Hamsher et al (2013).…”
Section: Biogeographic-ecological Remarksmentioning
confidence: 75%
“…Morphologically identical or "cryptic" species have been identified in the ecologically important diatom genus Thalassiosira [9,10]. Globally, Thalassiosira is one of the most abundant and diverse diatom genera [11] and includes species that are ecologically important components of phytoplankton communities in estuarine, coastal, and open ocean regions [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, community composition may be more accurately obtained through the use of molecular methods. For example, Hamsher et al [10] were able to classify more Thalassiosira species from individual cells and colonies using molecular methods than LM, including rarely occurring species. Metabarcoding, or the high-throughput sequencing of PCR amplicons from an entire community, has been used to identify diatoms, including Thalassiosira, from complex communities [21][22][23].…”
Section: Introductionmentioning
confidence: 99%